AN ANALYSIS OF THE RELEVANCE OF INSTRUCTIONAL MATERIALS AND THE TYPE OF TEACHING STRATEGIES USED FOR ADVANCED READING COURSE IN ENGLISH EDUCATION DEPARTMENT - ., Luh Melin Udayanti; ., Dra. Luh Putu Artini, MA., Ph.D.; ., Drs.Gede Batan,MA (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Penelitian ini merupakan penelitian deskriptif kualitatif yang bertujuan untuk menganalisis relevansi bahan ajar dan jenis strategi pengajaran yang digunakan untuk perkuliahan lanjutan Advanced Reading dalam jurusan pendidikan bahasa inggris. Subyek penelitian ini adalah mahasiswa yang telah mengambil perkuliahan lanjutan dari reading 1, reading 2, dan reading 3, dan dosen yang telah mengajar mata kuliah Advanced Reading di jurusan pendidikan bahasa inggris. Data dikumpulkan berdasarkan checklist, serta kuesioner dosen dan, dan juga hasil penilaiian dari para ahli serta diskusi kelompok dengan mahasiswa. Temuan penelitian menunjukkan bahwa bahan ajar dan silabus yang digunakan dalam perkuliahan Advanced Reading dikatakan "Sedikit relevan" untuk digunakan sebagai sumber belajar di jurusan pendidikan bahasa inggris. Strategi pengajaran yang sering digunakan dalam perkuliahan Advanced Reading adalah Diskusi. Hasil kuesioner dan diskusi kelompok dengan mahasiswa dari 6 (enam) kelas yang berbeda menunjukkan fokus tujuan pembelajaran Advanced Reading yang berbeda di setiap kelasnya disebabkan karena perbedaan materi pembelajaran yang diberikan oleh dosen. Penggunaan strategi pengajaran tidak memenuhi kriteria pelajar dewasa sehingga pembelajaran dianggap gagal untuk mendorong motivasi siswa dalam belajar.Kata Kunci : keterampilan membaca, bahan ajar, relevansi pembelajaran dan strategi mengajar This study was a descriptive qualitative research which aimed to analyze the relevance of instructional materials and the type of teaching strategies used for Advanced Reading course in English Education Department. The purpose was to describe the relevance of the syllabus and instructional materials, as well as the quality of these learning materials, and to find out the students perception of Advanced Reading course. The subjects of this research were the students who have taken Advanced Reading course and the lecturer who have taught Advanced Reading course in English Education Department. This research was a descriptive qualitative research which was utilizing checklist and questionnaire. The data collected from the expert judgesâ€™ checklist, as well as lecturer questionnaire and checklist, and also studentsâ€™ questionnaire and focus group discussion. The data obtained were descriptively analyzed. The finding of the research showed the relevance of Instructional Materials and the Advanced Reading syllabus was said â€œSlightly Relevantâ€ to be used as learning resource for English Education Department students. It showed that all experts choose more than 44% of criteria which had been reached. The teaching strategies that used frequently in Advanced Reading course was Discussion. The questionnaire result and the focus group discussion with the students from 6 (six) different classes showed different focus of learning objectives acquired by the students of each classes due to the differences of the learning material provided by the lecturer. The use of teaching strategies which also did not meet the criteria of adult learners was failed to encourage studentsâ€™ motivation of learningkeyword : reading skill, advanced reader, instructional materials, relevance materials, and teaching strategies